2016
DOI: 10.1159/000449433
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Analysis of Toxicity and Efficacy for 2 Hypofractionated Irradiation Schedules Versus a Conventional One for Post-Mastectomy Adjuvant Radiotherapy in Breast Cancer

Abstract: Introduction: The aim of this analysis was a retrospective evaluation of the efficacy and toxicity of 2 hypofractionated irradiation schedules compared to conventional therapy in post-mastectomy patients. Methods: 3 irradiation schedules were analyzed: 48.30 Gy in 21 fractions (group A, n = 60), 42.56 Gy in 16 fractions (group B, n = 27) and 50 Gy in 25 fractions (group C, n = 30) of the front chest wall. All groups were also treated with a supraclavicular field, with 39.10 Gy in 17 fractions (group A), 37.24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…However, HF-PMRT had a significant higher number of radiation boost patients than CF-HFRT ( p < 0.001); the late skin toxicity is also increase corresponding with a high dose delivery. The incidence rate of severe skin toxicity (grade 2 or higher) was comparable to other studies [15, 18–20], except for the Egyptian study [14]. The Egyptian study published grade 2 or higher skin fibrosis of 17% with the conventional radiation group, 33% in the 45 Gy in 17 fractions group, and 37% in the 40 Gy in 15 fractions group [14].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…However, HF-PMRT had a significant higher number of radiation boost patients than CF-HFRT ( p < 0.001); the late skin toxicity is also increase corresponding with a high dose delivery. The incidence rate of severe skin toxicity (grade 2 or higher) was comparable to other studies [15, 18–20], except for the Egyptian study [14]. The Egyptian study published grade 2 or higher skin fibrosis of 17% with the conventional radiation group, 33% in the 45 Gy in 17 fractions group, and 37% in the 40 Gy in 15 fractions group [14].…”
Section: Discussionsupporting
confidence: 73%
“…At the 7 year follow-up, no statistically significant difference in local recurrence (3, 1, and 2 patients, respectively) and mortality (4, 2, and 3 patients respectively) was found between the groups. Researchers in Greece compared conventional radiotherapy (50 Gy in 25 fractions) and hypofractionated radiotherapy (48.3 Gy in 21 fractions and 42.56 Gy in 16 fractions) and demonstrated that no patients developed a locoregional relapse with any of the treatment regimens [15]. However, this study had a short-term follow-up interval with a median time of 36 months.…”
Section: Discussionmentioning
confidence: 99%
“…5. Acute Skin Toxicity: Twenty-three studies [12,[14][15][16][17][18][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] reported acute skin toxicity in 3456 patients, and results showed no significant difference between the two groups (OR = 0.94, 95% CI = 0.67~1.32, P = 0.72, Fig. 3a).…”
Section: Meta-analysis Outcomesmentioning
confidence: 99%
“…7. Late Skin Toxicity: Seven studies [12,14,17,18,26,30,31] reported late skin toxicity in 1363 patients, and results showed no significant difference between the two groups (OR = 0.98, 95% CI = 0.75~1.27, P = 0.88, Fig. 3c).…”
Section: Meta-analysis Outcomesmentioning
confidence: 99%
“…Furthermore, the study regarding hypofractionated RT after mastectomy could be considered. Some investigators have suggested that hypofractionated RT is also an alternative option for PMRT [ 22 ], although it has not been thoroughly studied as in post-breast conserving surgery RT [ 23 25 ].…”
Section: Discussionmentioning
confidence: 99%